Rye and health - Poutanen, Kaisa; Åman, Per (AACC International, 2014)
Rye has been known to stimulate weight loss, prevent gallstones, lower the risk of type 2 diabetes, promote gastrointestinal health, and improve cardiovascular conditions. Due to rye s many health benefits, it s no wonder that nutritionists, the grains industry, and in turn consumers, have been giving this healthy grain much more attention. Rye and Health, edited by veteran food technology and nutrition scientists Kaisa Poutanen and Per Åman, explains in detail the composition of rye and its physiological and health effects on humans using the latest research and information available.--